2018
DOI: 10.18585/inabj.v10i1.331
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Pattern of Corynebacterium diphtheriae Isolated from Outbreaks in Indonesia 2010-2015

Abstract: BACKGROUND: Diptheria cases are treated with both anti-diphtheria serum (ADS) and antibiotics. Penicillin and erythromycin are the primary choices for any Corynebacterium diphtheriae (C. diphtheriae) infection. Antibiotic susceptibility pattern of C. diphtheriae has not been reported in Indonesia since 1982. The improper use of antibiotics, as well as, the consumption of antibiotics without prescription, will increase the resistance of C. diphtheriae. This study aims to determine the susceptibility pattern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
2
9
1
Order By: Relevance
“…Mitis biotypes were predominant in this study, similar to several results from France, [39], Algeria, [40], Malaysia, [41], Brazil, [3], United Kingdom, [15], and previous studies in Indonesia [42, 43]. In Poland and another study in United Kingdom, the majority of the biotypes were gravis [4, 44].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Mitis biotypes were predominant in this study, similar to several results from France, [39], Algeria, [40], Malaysia, [41], Brazil, [3], United Kingdom, [15], and previous studies in Indonesia [42, 43]. In Poland and another study in United Kingdom, the majority of the biotypes were gravis [4, 44].…”
Section: Discussionsupporting
confidence: 90%
“…Several experts and guidelines consider erythromycin as a drug of choice because it has better in vitro activity than penicillin, such as in the Vietnam study (MIC range, 0.025–0.05 mg/L) [5]. However, in other studies, erythromycin was reported to have high resistance [35, 43], while in our study, it was still susceptible in 85.2% of the isolates (92 of 108). Although 12% (13 of 108) of the isolates had decreased susceptibility but the resistance rates were relatively low, only 2.8% (3 of 108) had MIC of 2, 192, and > 256 μg/L.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…18 Engler et al (2000) in England also found that 405 of 410 isolates were sensitive, with MIC 0.026 μg/ml, and 5 others were resistant with MIC of 2-4 μ/ml. 19 Another study from Barraud et al in France using the Etest method showed the susceptibility of many antibiotics including Erythromycin against 46 isolates of Corynebacterium diphtheriae biovar mitis in the period from 1993 to 2010. 20 A study in Russia by Chagina et al using the Etest method showed that of 664 isolates between 1987-2013, most of them turned out to be sensitive to all antibacterial preparation, although 0.4-0.6% were intermediate and 4-4.4% were resistant to macrolide.…”
Section: Resultsmentioning
confidence: 99%